2013
DOI: 10.4236/pp.2013.42022
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Dried Blood Spot Samples in Screening Drugs of Abuse

Abstract: The present article will provide an overview of use of dried blood sampling method for analysis of drug of abuse. Relatively short half life and instability in blood, calls for alternative sampling method for determination of drugs of abuse. Dried blood spot (DBS) method has many advantages over the conventional sampling methods. The available method for DBS sample collection, storage and transport is described here. The techniques involved in and the factors that may influence the accuracy and reproducibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 21 publications
0
12
0
2
Order By: Relevance
“…These considerations are also important for sample collection in remote locations that may be without reliable access to a centrifuge and/or a freezer designated for biohazardous materials. Quantitative bioanalytical methods using the DBS methodology have been developed for genomic, metabolomic, and proteomic applications including newborn screening (3, 4), therapeutic drug monitoring (5, 6), toxicology and drugs of abuse (7,8), viral disease management (9, 10), and many others (2, 11).Targeted MS, in particular selected/multiple reaction monitoring (SRM/MRM) using internal standards, enables the rapid development of quantitative assays with high specificity, precision, and robustness (12-15). The integration of DBS sampling with MRM is well-established for quantifying a wide range of small molecules (16 -18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These considerations are also important for sample collection in remote locations that may be without reliable access to a centrifuge and/or a freezer designated for biohazardous materials. Quantitative bioanalytical methods using the DBS methodology have been developed for genomic, metabolomic, and proteomic applications including newborn screening (3, 4), therapeutic drug monitoring (5, 6), toxicology and drugs of abuse (7,8), viral disease management (9, 10), and many others (2, 11).Targeted MS, in particular selected/multiple reaction monitoring (SRM/MRM) using internal standards, enables the rapid development of quantitative assays with high specificity, precision, and robustness (12-15). The integration of DBS sampling with MRM is well-established for quantifying a wide range of small molecules (16 -18).…”
mentioning
confidence: 99%
“…These considerations are also important for sample collection in remote locations that may be without reliable access to a centrifuge and/or a freezer designated for biohazardous materials. Quantitative bioanalytical methods using the DBS methodology have been developed for genomic, metabolomic, and proteomic applications including newborn screening (3,4), therapeutic drug monitoring (5,6), toxicology and drugs of abuse (7,8), viral disease management (9,10), and many others (2,11).…”
mentioning
confidence: 99%
“…Urinary VOC metabolites are suitable biomarkers of exposure to VOCs because they have longer physiological half-lives and are less volatile than the parent compounds [8]. Urinary metabolites often have poor stability; the issue of instability during sample transportation and storage poses a challenge in the interpretation of analytical results [10]. The use of the dried urine spot (DUS) technique is an alternative approach because the DUS does not contain water as a medium to promote chemical decomposition reactions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The use of the dried urine spot (DUS) technique is an alternative approach because the DUS does not contain water as a medium to promote chemical decomposition reactions [11,12]. Compared with wet urine analysis, DUS sampling reduces sample handling issues, the cost of transportation, and the risk of contamination [10,11]. The DUS is generally eluted by solvent extraction using methanol, acetonitrile, water, or mixtures of these solvents, and several applications such as newborn screening have been developed and practically implemented [11,[13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There is a dearth of published research regarding usage of urine spotted dried samples for screening drug of abuse in patients with substance use disorders from field settings, though reviews of dried blood spot (DBS) are available. [ 8 9 10 11 12 ] To the best of our knowledge, no study has reported the use of DUS for detection of BZD.…”
Section: Introductionmentioning
confidence: 99%